1983
DOI: 10.3109/00016348309154226
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Delivery Subsequent to Vacuum ‐ Aspiration Abortion in Nulliparous Women

Abstract: Altogether 4719 women who had had a legally induced abortion in Uppsala County during 1970-75 were followed by means of computerized record linkage, and deliveries during 1970-78 after abortion were noted. Out of 1 364 deliveries traced, 670 were to primiparas who had had a previous vacuum-aspiration (VA) abortion. The outcome of the delivery for the 670 women was compared with that of matched controls, 622 primiparas and 626 secundiparas. Confounding variables were checked for by multiple regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…No association between induced abortion and LBW was confirmed by many other investigators (Meirik et al, 1982;Linn et al, 1983;Meirik et al, 1983;Frank et al, 1985;Mandelson et al, 1992).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…No association between induced abortion and LBW was confirmed by many other investigators (Meirik et al, 1982;Linn et al, 1983;Meirik et al, 1983;Frank et al, 1985;Mandelson et al, 1992).…”
Section: Discussionsupporting
confidence: 57%
“…A number of investigators have studied the effect of previous induced abortion on LBW in subsequent pregnancies, but with conflicting results. Most of the earlier studies indicated no increased risk of LBW following an induced abortion (Meirik et al, 1982;Linn et al, 1983;Meirik et al, 1983;Frank et al, 1985;Mandelson et al, 1992), but later studies have reported a significantly elevated risk of LBW following a previous induced abortion ( Lekea-Karanika et al, 1994;Okonofua et al, 1994). Since the risk may depend upon hospital routines and the health of women who seek an induced abortion, updated studies are needed.…”
Section: Introductionmentioning
confidence: 95%
“…Scandinavian studies largely overcome these methodological limitations by identifying subjects through cross-linked birth and abortion registries. In one such study the authors [25] matched 670 primiparas with a prior vacuum abortion to 622 primiparas and 626 secundiparas who had had no abortions; they found no significant difference in obstetrical outcomes. In a more recent registry-linked study [26], the frequency of preterm delivery was significantly higher in women with histories of induced or spontaneous abortion only when the interpregnancy interval exceeded 12 months; this study did not control for socioeconomic status or smoking during pregnancy.…”
Section: Comparison Of Labor Induction Versus Dande Abortionmentioning
confidence: 99%
“…At operation, no perforation of the uterus, no cervix laceration and no bleeding exceeding 300 ml occurred which probably indicates that the induced cervical dilatation and uterine tonus reduces the risks for such complications. Preoperative treatment with vaginal suppositories containing 15-methyl-PGFk methyl ester may reduce the complication rate in subsequent pregnancies, but recent studies (6,14) have failed to demonstrate any adverse effect without such pretreatment.…”
Section: Discussionmentioning
confidence: 99%